Pemahaman Hadis Misoginis dalam Kitab Uqudul Lujayn di Pondok Pesantren An-Nur Semarang - Akhmad Khozin (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
This research is based on the problems in society related to the rights and roles of women who are neglected, because the indications of Hadith misogynically interpreted by classical commentators, on the one hand upholds the dignity of women, but on the other hand castrates women's rights by limiting the women's role in marriage life and closing their steps to contribute in the environment. The purposes of this study are; (1) to know the extent to which the students' understanding of the Hadiths studied in uqudul lujayn book; (2) to dig into the understanding built in the study of the lqliya texts related to the misogynical Hadith; (3) to imply the understanding to everyday life. The method used in this study is a qualitative method by presenting data through verbal and then changed into description form, not numbers. The results showed that; (1) the santri who studied lqya lujayn book initially did not understand the existence of the misogynous Hadith and only understood the book and the teacher's information, after in-depth study, the students sought to re-understand by combining; (2) in the classical and hermeneutic method of interpretation can be understood that there is no misogynist Hadith, but Hadits misogynically interpreted; (3) the understanding is implied on the activities of santriwati an-Nur in everyday life.